Analysis of the effect of bank size, credit risk, and capital adequacy on cost efficiency of banks in Indonesia (SFA method) - Nainggolan, Romauli; Sari, Dyah Wulan; Wasiaturrahma, Wasiaturrahma (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2022)
Many banks are competing to achieve bank cost efficiency for business continuity amidst the competition in the banking sector. So banks need to review cost-efficiency regularly. The purpose of this study was to analyze determinants of bank cost efficiency. Variable use bank size, capital adequacy, return on asset, group of the bank, credit risk, economic growth, and inflation on bank cost efficiency in Indonesia. Determination of bank input and output variables using a bank intermediation approach. This study used panel data on 38 banks in Indonesia for the period 2012-2018. This paper used the Stochastic Frontier Analysis (SFA) analysis method. The results of this study reveal four things. First, bank size has a negative effect bank cost efficiency. Second, credit risk has a positive effect on bank cost efficiency. Third, capital adequacy has a positive effect on bank efficiency. Fourth, the small core capital bank group has a negative effect on bank cost efficiency. Bank external variables do not affect bank cost efficiency in Indonesia.